ANALISIS DETERMINAN AGRESIVITAS PAJAK: LEVERAGE, PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, DAN UKURAN PERUSAHAAN (Studi pada Emiten di Kompas100 Periode 2015-2017) - Fiarniah, Dini; Hapsari, Dini Wahjoe; Aminah, Wiwin (Aksara Public, 2018)
This study aims to analyze the factors that can affect tax aggressiveness. In this study, leverage variables, disclosure of corporate social responsibility, and company size were used. This study intends to determine the effect of leverage, disclosure of corporate social responsibility, and company size on tax aggressiveness simultaneously and partially. This research is a study using quantitative research methods with the purpose of descriptive-causative nature. The unit of analysis that is the focus of this research is the company that is consistently registered in Kompas100 for the period 2015-2017 with a purposive sampling technique. This study uses 36 research samples for three years of research and uses panel data regression analysis with EViews 9. The results of the study show that leverage, disclosure of corporate social responsibility, and company size have an effect on simultaneous tax aggressiveness. Partially, the leverage variable and disclosure of corporate social responsibility affect the aggressiveness of the tax, while the size of the company does not affect tax aggressiveness.